Batman forever? : the economics of overlapping rights - Cuntz, Alexander; Kaiser, Franziska (World Intellectual Property Organization, 2020)
When copyrighted comic characters are also protected under trademark laws, intellectual property (IP) rights can be overlapping. Arguably, registering a trademark can increase transaction costs for cross-media uses of characters, or it can help advertise across multiple sales channels. In an application to book, movie and video game publishing industries, we thus ask how creative reuse (innovation in uses) is affected in situations of overlapping rights, and whether 'fuzzy boundaries' of right frameworks are in fact enhancing or decreasing content sales.
"October 2020."
Keywords: Intellectual property -- Economic aspects.; Intellectual property (International law); Intellectual property -- Interpretation and construction.; Comic art paraphernalia.